Determination of cocaine in samples of hair using the chromatographic column, ISRP-C-18 - Menezes, Manoel Lima de [UNESP]; Muzardo, G. A.; Chaves, M. S. (Marcel Dekker Inc, 2004)
A method has been developed for the determination of the cocaine levels in samples of hair, using a chromatographic column internal surface reverse phase (ISRP)-C-18, for direct injection of the extracts of hair, without purification or derivation of the sample. The method allows monitoring an individual stopped for using or making cocaine. This method allowed the determination of levels of cocaine concentration in 75% of the analyzed samples of chemical dependents' hair, with cocaine detected at levels of 0.37-16.85 mug g(-1). In the other analyzed samples (25%), the drug was not detected, because the corresponding individuals told us that they consumed cocaine infrequently and in small amounts. The detection
Keywords: cocaine; ISRP-column; hair; HPLC